Analysis the Level of Passenger Satisfaction with Community Services at Terminal Type A Purabaya using Service Quality Methods - Vanesha N.M Simanjuntak; Dira Ernawati (Yayasan Kita Menulis, 2025)
Terminal Tipe A Purabaya is an institution providing various types of land transportation services under the Ministry of Transportation. The main issue faced by the Type A Purabaya Terminal lies in improving the quality of public service to meet expectations and enhance passenger satisfaction. The Service Quality (Servqual) method is employed, with validity and reliability testing conducted using SPSS software. Data analysis reveals a gap between the actual performance experienced by passengers and their expectations regarding services at the Type A Purabaya Terminal. Based on the calculations, it can be concluded that there is a discrepancy between service expectations and the actual performance at the terminal. The analysis identifies nine attributes with negative gap values, indicating that the services received by passengers remain unsatisfactory. The attributes requiring improvement include bus departure and arrival schedules, staff knowledge of routes and schedules, the accuracy of information provided by staff, facilities for the elderly and disabled, as well as various other aspects related to comfort, safety, and cleanliness of the facilities. Through the Service Quality analysis, the Type A Purabaya Terminal can prioritize service attributes that need enhancement and design effective improvement strategies. This will ensure continuous service improvements aligned with passenger expectations.